Nepal’s First Laser Bronchoscopy: A Case Report - Sapkota, Ranjan; Shrestha, Bibhush (Journal of Institute of Medicine Nepal, 2021)
Light Amplification by Stimulated Emission of Radiation (Laser) is an essential tool for a thoracic surgeon in the management of tracheobronchial lesions: alone or on combination with other modalities of treatment. Post-tracheostomy tracheal stenosis (PTTS) is a well-known entity and often a challenging problem to manage. Here we report a successful use of endotracheal Laser, yet unreported in available English Literature from Nepal, in a 24 year man with PTTS after a protracted hospital stay for traumatic brain injury. The use of Laser bronchoscopy in such cases is safe and feasible, alone or in combination with tracheal dilatation.